How the perfectionistic climate of a sports team predicts the athletic performance of elite athletes: a case study of the CUBAL women`s basketball team - Meng, M.; Su, R.-H.; Kogiso, K.; Zheng, R.-R.; Chen, L.; Wei, W.; Li, W.; Hsu, M.-C. (Frontiers in Psychology, 2024)
Objective: In competitive sports, understanding how the perfectionistic climate within teams influences the performance of elite female athletes can provide valuable insights for enhancing coaching practice and athletic achievement. Based on the cognitive appraisal theory of stress, this study constructs a dual-path model using stressors and coping strategies as mediators, referred to as the Perfectionistic Climate on Athletic Performance model (PCPM). The study explores the predictive role of the perfectionistic climate within sports teams on the athletic performance of elite female basketball players.